Dwa pojęcia refleksyjności w antropologii Karola Wojtyły - Kubiak, Maria (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The aim of this article is to reconstruct and analyze Karol Wojtyła’s philosophical conception of reflectiveness as exposed in his book Osoba i czyn (eng. The Acting Person). There are two general aspects of reflectiveness - theoretical and practical; this paper is focused mainly on the first. The analysis is composed of three sections. Firstly, the philosophical context of reflectiveness is presented by depicting general philosophical meaning of the term and juxtaposing it with Wojtyła’s anthropological views. Next, Wojtyła’s concept is reconstructed. Finally its moral and existential validity is signalized.
Keywords: awareness; consciousness; interiorization; Karol Wojtyła; knowledge; reflection; reflectiveness; self-knowledge